HEALTHCARE MANAGEMENT AS A KEY COMPONENT OF SUSTAINABLE DEVELOPMENT: A COMPARATIVE ANALYSIS OF SERBIA AND SLOVENIA - Ilic, Djordje; Andžić, Slobodan; Erić, Dragan (Economics of Agriculture, 2025)
This study explores the role of health management as a driver of sustainable rural development in Serbia and Slovenia. Using quantitative methods (cluster, correlation, and regression analyses), it compares perceptions of health management and its impact on local communities. Results show that health management is positively perceived and linked to economic diversification, user satisfaction, and infrastructure quality. Slovenia performs better in accessibility and diversity of health services, reflecting its advanced institutional framework, while Serbia emphasizes marketing management, digital literacy, and economic benefits, indicating a growth phase. Strong correlations between health management and sustainable development dimensions confirm that effective health management improves rural well being. Economic impact and user loyalty are the strongest predictors of development outcomes. Findings highlight the need for tailored policies addressing demographic and ecological challenges and fostering cross-country learning. The study recommends further research to maximize health management’s contribution to rural sustainability and inform policymakers and stakeholders.